2013
DOI: 10.1149/2.010305jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atomic Layer Deposition Temperatures on TiO2/n-Si MOS Capacitor

Abstract: This paper reports on the influence of deposition temperature on the structure, composition, and electrical properties of TiO 2 thin films deposited on n-type silicon (100) by plasma-assisted atomic layer deposition (PA-ALD). TiO 2 layers ∼20 nm thick, deposited at temperatures ranging from 100 to 300 • C, were investigated. Samples deposited at 200 • C and 250 • C had the most uniform coverage as determined by atomic force microscopy. The average carbon concentration throughout the oxide layer and at the TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 30 publications
4
14
0
1
Order By: Relevance
“…Figure 7d shows the dark J-V curve in semi-logarithmic scale under positive and negative biases at room temperature. As can be seen, the leakage current density at −2 V is in the order of 10 −5~1 0 −4 A/cm 2 , which is in the same order of magnitude reported by Wei et al [5] and Baek et al [1] that used PEALD and tetrakis dimethylamino titanium (TDMAT) as precursor to growth TiO 2 (20 nm) on Si.…”
Section: Current Density-voltage Measurementssupporting
confidence: 81%
See 2 more Smart Citations
“…Figure 7d shows the dark J-V curve in semi-logarithmic scale under positive and negative biases at room temperature. As can be seen, the leakage current density at −2 V is in the order of 10 −5~1 0 −4 A/cm 2 , which is in the same order of magnitude reported by Wei et al [5] and Baek et al [1] that used PEALD and tetrakis dimethylamino titanium (TDMAT) as precursor to growth TiO 2 (20 nm) on Si.…”
Section: Current Density-voltage Measurementssupporting
confidence: 81%
“…The increase of oxygen content in PEALD TiO 2 films may be related to the higher reactivity of O 2 plasma compared to the water precursor used in thermal ALD. In a recent study, Wei et al [5] showed the influence of temperatures on the PEALD process applied to the growth of TiO 2 films in Si for the manufacture of MOS capacitors, where they used O 2 plasma at 400 W of RF power. They varied the temperature from 100 to 300 • C, with steps of 50 • C. Using the X-ray photoelectron spectroscopy (XPS) technique, they verified that the TiO 2 films had O/Ti stoichiometry ranging from 2.08 to 2.32.…”
Section: Structure and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Table 1 shows a comparison of the physical and electrical properties of the anatase TiO 2 films obtained by various methods like DC sputtering, PECVD, ALD and LTAVD with the present work [33][34][35][36]. The results demonstrate that the TiO 2 films obtained by the present protocol showed comparable dielectric constant and very low leakage currents with excellent surface morphology.…”
Section: Current-voltage Characteristicsmentioning
confidence: 51%
“…x [561,683,[735][736][737][738][739][740][741][742][743]; [384,646,744]; [384,646,651,741,[745][746][747][748][749][750][751][752][753][754][755][756][757][758][759][760][761];…”
Section: Alkoxidesunclassified